Price Spread, Farmer Share, and Marketing Channels in the Pigeon Pea Value Chain in Maharashtra State of India - Kadam, Sachin; Kajale, Dilip; Malik, Sushant (Research on World Agricultural Economy, 2026)
Pigeon pea is one of the important crops in terms of area and production in Maharashtra, India, contributing about one-third of India's total pigeon pea production. It is also an important source of protein in Indian households. The present study focuses on a comprehensive analysis and mapping of the value chain of pigeon pea in Maharashtra. A multi-stage stratified sampling method was used in the study. Primary data was collected from 560 farmers and 149 other important stakeholders. The value chain mapping technique was used for visualisation and quantification. We found that the average cost of production was Rs. 3785 per quintal, and the benefit-cost ratio was 1.57, indicating economic viability. Five major marketing channels were identified. A majority of farmers (88.8%) sold their produce to commission agents at nearby government-regulated markets. The farmers' share in the consumer's price was between 65–74% across the channels. The price spread range was 35–55%, with the highest value addition (16–34%) occurring at the processor level. The lowest price spread (35%) was reported in a channel, which involves farmer-producer companies (FPC), and this channel not only gives farmers a higher share (74.16%) but also offers consumers a lower price. Our study is one of the few that compares FPC-led and traditional channels, reporting the quantification of benefits across the different marketing channels of pigeon pea. The policy recommendation is that the government should focus on post-harvest management and strengthening of FPCs, through partnering with private sector and non-governmental organisations. ER